The civil war in art and memory - Savage, Kirk 1958- (Studies in the history of art (Washington, D.C.), 2016)
"Reflecting on the sesquicentennial of the American Civil War, this notable book brings together a range of media and perspectives that show how the conflict has been recorded and remembered over time. Fifteen essays written by leading scholars in a variety of disciplines explore visual representations of the war and its remembrance from the mid-19th century to the present. The text is organized in four sections on the themes of home, the battlefield, public space, and heroism."--Publisher's website